Interrogating the Essential Bacterial Cell Division Protein FtsQ with Fragments Using Target Immobilized NMR Screening (TINS) - Glas, Marjolein (Int J Mol Sci, 2019)
The divisome is a large protein complex that regulates bacterial cell division and therefore represents an attractive target for novel antibacterial drugs. In this study, we report on the ligandability of FtsQ, which is considered a key component of the divisome. For this, the soluble periplasmic domain of Escherichia coli FtsQ was immobilized and used to screen a library of 1501 low molecular weight (< 300 Da), synthetic compounds for those that interact with the protein. A primary screen was performed using target immobilized NMR screening (TINS) and yielded 72 hits. Subsequently, these hits were validated in an orthogonal assay. At first, we aimed to do this using surface plasmon resonance (SPR), but the lack of positive control hampered optimization of the experiment. Alternatively, a two-dimensional heteronuclear single quantum coherence (HSQC) NMR spectrum of FtsQ was obtained and used to validate these hits by chemical shift perturbation (CSP) experiments. This resulted in the identification of three fragments with weak affinity for the periplasmic domain of FtsQ, arguing that the ligandability of FtsQ is low. While this indicates that developing high affinity ligands for FtsQ is far from straightforward, the identified hit fragments can help to further interrogate FtsQ interactions.